Verdad histórica y verdad procesal. Felipe Rodríguez Moreno (2016). Quito: Cevallos Editora Jurídica - Estrada Proaño, Ramiro (Iuris Dictio, 2017)
Verdad histórica y verdad procesal. Felipe Rodríguez Moreno (2016). Quito: Cevallos Editora Jurídica.